Comparative Study of Manakib Nurul Burhani Book with Jawahirul Maani and The Teachings of Sufism in the Book Hagiography - Moh Ashif Fuadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
Most of the people, especially nahdliyin residents, still follow the practice of manakib Sheikh Abdul Qadir al-Jailani. They do this to obtain the blessings of life. There are two most significant mainstream works in the reading of manakib, and the first is the book Nurul Burhani by K.H. Muslih Mranggen, and the second is the book of Jawahirul Ma’ani by K.H. Jauhari Umar Pasuruan. Each is read by many practitioners of manakib, which basically explains the biography of Abdul Qadir al-Jailani. This research is a comparative study of the historical two books by the method of library study. The results of this study are that books with each other have similarities and differences, even similarities in the content and editorial side. In a historical review, the authorship of the book influences by the experiences of different authors. Nurul Burhani’s book consists of eight parts, while the book of Jawahirul Ma’ani has ten features. Each has a lot in common in the teachings of Sufism that Always act on the truth, a figure is always connected with God at the time of dhikr and live the laws of God and be founded the teaching of Sufism like mujahadah, riyadhah, wara’, zuhud, khauf, qona’ah, sabar, syukur, muraqabah.